Granted - Anderson, John David 1975- (New York, NY Walden Pond Press, 2018)
The Granter fairy Ophelia Delphinium Fidgets is one of the fairies whose job is to go outside of the Haven and grant unsuspecting humans their wishes. The Granters' work is what generates the magic for the rest of the fairies. It is Ophelia's first day, and she is going to learn that in the real world it takes more than fairy-dust to get what you truly want.
School Library Journal Starred
Publishers Weekly
Booklist
800
4-6.
5.5.
Keywords: Fantasy fiction; Fantasy; Wishes -- Fiction; Magic -- Fiction; Fairies -- Fiction